1997
DOI: 10.1093/bja/78.1.97
|View full text |Cite
|
Sign up to set email alerts
|

Effect of low-dose dopamine on serum concentrations of prolactin in critically ill patients

Abstract: Dopamine is a naturally occurring catecholamine with actions in the central nervous system and endocrine systems, including inhibition of prolactin release from the pituitary gland. Prolactin secretion has been shown to be increased in response to physiological stress, while hypoprolactinaemia is associated with a reduction in the cellular immune response. We have investigated the effects of low-dose infusion of dopamine 2.5 micrograms kg-1 min-1 on serum concentrations of prolactin in critically ill patients.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
2

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 6 publications
0
18
0
2
Order By: Relevance
“…We observed no difference in the need for renal support therapy in our study between dopamine-treated patients and other patients. Fourth, dopamine administration can reduce the release of a number of hormones from the anterior pituitary gland, including prolactin (17,18), which can have important immunoprotective effects. The tendency toward a higher incidence of ICU-acquired infection in dopamine-treated patients in our study may favor this mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…We observed no difference in the need for renal support therapy in our study between dopamine-treated patients and other patients. Fourth, dopamine administration can reduce the release of a number of hormones from the anterior pituitary gland, including prolactin (17,18), which can have important immunoprotective effects. The tendency toward a higher incidence of ICU-acquired infection in dopamine-treated patients in our study may favor this mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that dopamine may alter the inflammatory response in septic shock by decreasing the release of a number of hormones, including prolactin (41). Other potentially harmful endocrine effects have been demonstrated in trauma patients (42)(43)(44)(45).…”
Section: Rationalementioning
confidence: 99%
“…Dopamine-induced PRL suppression was widely documented over the past 20 years in adults, children and neonates [32,80,202,208,[260][261][262][263]. As far as now, few evidences exist for preterm newborns, especially for VLBW infants, and only recently the eventual PRL suppression in this population assumed broadening relevance [80].…”
Section: B Dopamine Treatment and Prl Secretion In Neonates And Vlbwmentioning
confidence: 99%